Strengthening Organizational Resilience through Strategic Collaboration among Educators in Educational Institutions with a Mixed-Methods Approach - Pierre Marcello Lopulalan (Sakura Digital Nusantara, 2026)
This study examines how strategic collaboration among educators strengthens organizational resilience in educational institutions. In the context of rapid educational reforms, digital transformation, and institutional uncertainty, schools must develop adaptive systems to sustain performance. This study employed a mixed-methods design using a sequential explanatory approach. Quantitative data were collected from 150 respondents consisting of teachers, principals, and educational staff in primary and secondary schools in West Java, Indonesia, selected using purposive sampling based on their involvement in collaborative activities. The instrument used a five-point Likert scale to measure strategic collaboration and organizational resilience. Data were analyzed using descriptive statistics and multiple regression. The results show that strategic collaboration has a significant positive effect on organizational resilience (R = 0.71; R² = 0.50; p < 0.001), indicating that collaboration explains 50% of the variance in resilience. Qualitative data from 20 participants, analyzed thematically, reveal that shared decision-making, open communication, and collective problem-solving are key mechanisms supporting resilience, reinforced by leadership support and a culture of trust. This study contributes by demonstrating that organizational resilience is a collective and structurally developed capability. The novelty lies in integrating strategic collaboration and resilience within a mixed-methods framework. Practically, the findings highlight the importance of institutionalizing collaboration, strengthening participatory leadership, and fostering trust-based organizational cultures to enhance adaptive capacity.